The Effect of Price Education on Changes in Perceptions and Purchasing Decisions of Bella Square Hijab for UINSU Students - Harahap, Isnaini; Nurbaiti, Nurbaiti; Syahfitri, Rizky Ananda; Rangkuti, Sari Jamila (Universitas Islam Negeri Sumatera Utara, 2024)
This article is about training about price education on the purchasing decisions of Bella Square hijabs among female students at the State Islamic University of North Sumatra (UINSU). Bella Square hijabs, known for their simple square design and affordable pricing, have seen a significant increase in sales from 2020 to 2021. The methodology involves Focus Group Discussions and coaching to understand how price and quality influence the purchasing interest of female students. Primary data was collected from 50 respondents who have purchased Bella Square hijabs. The results indicate that while the affordable price has attracted many buyers, it is crucial for the company to balance price and quality to maintain the product's market appeal. Understanding how price affects consumer value perception can assist producers in developing more effective marketing strategies, such as offering discounts, loyalty programs, and utilizing social media for promotion. Additionally, paying attention to the quality of materials and designs that align with current fashion trends is essential to capture the interest of female students. The findings of this article provide insights for producers to optimize marketing strategies and maintain consumer loyalty amid increasing competition.